2019
DOI: 10.1093/ageing/afz054
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a frail older person: the association between informal caregiver burden and being unsatisfied with support from family and friends

Abstract: Background/objective although informal caregivers (ICG) find caring for a relative mainly satisfying, it can be difficult at times and it can lead to a state of subjective burden characterised by -among others- fatigue and stress. The objective of this study is to analyse the relationship between perceived social support and subjective burden in providing informal care to frail older people. Methods a descriptive cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
(33 reference statements)
3
28
1
5
Order By: Relevance
“…Therefore, it was surprising to find that the prevalence of depressive and tension-related symptoms was so high in our Swedish caregiver population. Depressive mood was reported by 27.6% of the male caregivers and 39.2% of the females (data not shown), which should be compared to a Belgian study looking at caregivers to frail, elderly people where 11–22% of caregivers reported feelings of depression and anger [ 25 ], or a Norwegian study where 18% male and 30% female caregivers to cancer patients reported depressive symptoms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was surprising to find that the prevalence of depressive and tension-related symptoms was so high in our Swedish caregiver population. Depressive mood was reported by 27.6% of the male caregivers and 39.2% of the females (data not shown), which should be compared to a Belgian study looking at caregivers to frail, elderly people where 11–22% of caregivers reported feelings of depression and anger [ 25 ], or a Norwegian study where 18% male and 30% female caregivers to cancer patients reported depressive symptoms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gender differences found in our study population could be explained by physiological and social aspects. In a caregiving context, coping mechanisms, social support, and socioeconomic factors have all been shown to affect perceived burden [ 22 , 25 ]. Gender and socioeconomic inequalities were reported from a Spanish nationwide survey [ 21 ] where women had less access to formal support.…”
Section: Discussionmentioning
confidence: 99%
“…Informal care is usually provided by a family member in the same age group as the care recipient (generally a wife or daughter) 3 . Besides facing their own aging process and health problems 4 , these individuals must deal with a variable and increasing load of tasks throughout the care process 5 .…”
Section: Introductionmentioning
confidence: 99%
“…24 In Belgium, perceived greater social support from family and friends is related to lower informal caregiver burden. 25 In this perspective, the NYUCI, with its unique emphasis on the maximisation of social support for informal caregivers could also work well in the Flemish context. Therefore, we will develop a Flemish adaptation of the NYUCI for the target group of informal caregivers of older people with early cognitive decline.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%